Patterns of failure after radiotherapy for pediatric patients with intracranial ependymoma. Issue 3 (March 2017) - Tensaouti, Fatima; Ducassou, Anne; Chaltiel, Léonor; Bolle, Stéphanie; Muracciole, Xavier; Coche-Dequeant, Bernard; Alapetite, Claire; Bernier, Valérie; Claude, Line; Supiot, Stéphane; Huchet, Aymeri; Kerr, Christine; et al.
Abstract: Purpose: To investigate the patterns of failure after radiotherapy for pediatric intracranial ependymoma and their correlation with dose parameters. Methods: Between 2000 and 2013, 206 patients were treated in France. MRI scans at relapse were registered to the original planning CTs for topographic analysis of failure patterns. To compare relapse patients (RP) with non relapse patients (NRP), several dose parameters were derived from dose volume histograms. Results: Over a median follow-up of 53.8 months, 84 patients presented with relapse. Topographic analysis showed 50 patients with local relapse in the radiation field, 6 in the edge of field, 6 locoregional outside the field, 10 in the spine, 5 supratentorial and 7 local and distant. The median coverage, target coverage and homogeneity indices did not differ significantly between RP and NRP. The median volume of in-field relapse was 1.25 cc [0.11, 27], with a median dose of 57.83 Gy [50.04, 61.69]. Conclusions: Local relapse in the tumor bed and the higher dose regions was the predominant pattern of failure. Improving coverage of the target volume and increasing the dose to the high radioresistant regions, taking into consideration other clinical and biological pronostic factors, may be an effective way of reducing local failures.